The Improvement of Students’ Adaptive Reasoning through Connected Mathematics Project Model on Vocational High School PP Kutacane - Wati, Merna (IKIP Siliwangi, 2025)
The development of students' adaptive reasoning is a critical aspect of mathematics education, especially in preparing students to solve complex, real-world problems. The purpose of this study is to explore the effectiveness of the Connected Mathematics Project (CMP) model in improving the adaptive reasoning of Class X students at SMK PP Negeri Kutacane. This study used a classroom action research approach, conducted over two cycles, each consisting of three meetings (6x45 minutes). Each cycle included four stages: planning, action, observation, and reflection. In Cycle I, the CMP model was implemented, and students worked on problems that encouraged adaptive reasoning. Cycle II followed the same structure, with continued use of the CMP model and a focus on evaluating student progress. The results showed a significant improvement in student learning outcomes, with the class average increasing from 53.71 in the pre-cycle to 61.38 in Cycle I and 84.19 in Cycle II. The percentage of learning completeness also improved, from 9% in the pre-cycle to 47.61% in Cycle I and 83.33% in Cycle II. This indicates that the CMP model effectively enhanced students' adaptive reasoning. The study concludes that the CMP model is a promising method for improving students' mathematical reasoning and learning outcomes, but further research is needed to explore its broader applications in other educational contexts.